2019
DOI: 10.7150/thno.36838
|View full text |Cite
|
Sign up to set email alerts
|

CACYBP Enhances Cytoplasmic Retention of P27Kip1 to Promote Hepatocellular Carcinoma Progression in the Absence of RNF41 Mediated Degradation

Abstract: Calcyclin-binding protein (CACYBP) is a multi-ligand protein implicated in the progression of various human cancers. However, its function in hepatocellular carcinoma (HCC) remains unknown.Methods: The expression of CACYBP and RNF41 (RING finger protein 41) in HCC cancer and adjacent non-tumor tissues was detected by immunohistochemistry. CCK-8 assays, colony formation assays, flow cytometry detection and xenograft models were used to evaluate the impact of CACYBP expression on HCC cell growth, apoptosis and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 52 publications
1
22
1
Order By: Relevance
“…CACYBP is up-regulated in HCC compared to normal liver tissues and is related to poor prognosis in HCC patients. It contributes to the development and progression of HCC and may serve as a promising therapeutic and prognostic biomarker [ 42 ]. RAET1E belongs to a ligand family for NKG2D in humans and can produce a soluble, 35-kDa protein (named RAET1E2) in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…CACYBP is up-regulated in HCC compared to normal liver tissues and is related to poor prognosis in HCC patients. It contributes to the development and progression of HCC and may serve as a promising therapeutic and prognostic biomarker [ 42 ]. RAET1E belongs to a ligand family for NKG2D in humans and can produce a soluble, 35-kDa protein (named RAET1E2) in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, NDRG1 has been reported to be an essential molecule in controlling the metastasis and recurrence of HCC [44]. In addition, the deletion of CACYBP has also been reported to increase apoptosis of HCC cells [45], while the variants of OSGIN1 could reduce apoptosis and are associated with shorter survival [46]. Besides, knockdown and overexpression assays have demonstrated that PSMD14 could promote migration and invasion of HCC cells in vitro, and facilitate tumor growth and metastasis in vivo [47].…”
Section: Discussionmentioning
confidence: 99%
“…Lee's et al study [ 21 ] found that HSPD1 was downregulated during early apoptosis of the hepatoma cell mediated by Paeoniae Radix. In terms of CACYBP , it has been verified that CACYBP can promote hepatocellular carcinoma progression in the absence of RNF41 -mediated degradation [ 22 ]. Moreover, a study [ 23 ] found that PNP /fludarabine suicide gene system induced HCC cell apoptosis and inhibited the growth of HCC cells.…”
Section: Discussionmentioning
confidence: 99%